Financial Feasibility of Te'tekan Cake Business - Musdalifa Musdalifa; Astrini Padapi; Ayu Wulandary (Agribusiness Journal, 2025)
Financial feasibility of Te'tekan traditional cake business, This study aims to analyze the financial feasibility of Te'tekan traditional cake business in Enrekang Regency. The study was conducted in Mampu Village, Anggeraja District, which is known as the center of Te'tekan cake production. The method used is a quantitative approach with data collection through questionnaires and interviews with informants who have been running the business for more than five years and have a larger production scale than similar businesses. The feasibility analysis was carried out using the Net Present Value (NPV) and Internal Rate of Return (IRR) methods. The results showed that the total production cost for one year was IDR901,315,000, with total revenue reaching IDR2,849,157,000, resulting in a net income of IDR1,947,842,000. The NPV value obtained was IDR5,628,240,951 and the IRR was 55%, which was much higher than the assumed discount rate of 15% and 20%. Thus, the Te'tekan cake business is considered financially feasible and has promising business prospects to be developed in the future as part of strengthening local food and regional economic growth.